Communication: a key element in fostering a sense of belonging and participation in a saving and credit cooperative - Peláez Osorio, Daniel Augusto (2026)
This article analyzes the influence of internal communication on the sense of belonging and participation of members of a saving and credit cooperative in Mexico (2024-2025). A mixed method descriptive-exploratory approach was used to analyze each component of the phenomenon and achieve a comprehensive understanding. The quantitative results revealed the relationship between the studied variables and confirmed the hypothesis. Simultaneously, qualitative data analysis, aside from reiterating this connection, delved into the members’ perceptions and experiences regarding internal communication, sense of belonging and participation, and how they vary according to their role and other factors. It was concluded that, despite the internal communication has made considerable progress and the current channels are effective in some aspects and between certain departments, there are opportunities for improvement in the development of the cooperative.